Sie sind auf Seite 1von 6

GROUP 2 SUMMARIZATION by (11 STEM C) CABBIGAT, Jinky Mae

GUABNA, Abbie Joy


KITONG, Christine Mae
PUGONG, Ceshanie
BUYUCCAN, Rainier Homar
MANGALLAB, Julio Mark

LOGARITHM IN EXPANDED FORM AND AS A SIMPLE LOGARITHM (AND VICE


VERSA)
In order to find the solution of logarithmic equations, we must first know how to expand each
expression and ofcourse the laws of logarithms, especially the Product Rule, Quotient Rule, and the Power
Rule; and the Laws of Exponents.

Expressing a single log in expanded form


a. log 4 𝑥² y (or log 4 𝑥² • 𝑦 -> a product of factors) = 2 log 4 𝑥 + log 4 𝑦 (or
2 • log 4 𝑥 + log 4 𝑦)
-> From multiplication to addition and vice versa-> Product Rule; and the exponent to a co-
efficient-> Power Rule)

b.
2
𝑥 𝑦
log 5 [ 3 ] = 2 log 5 𝑥 + log 5 𝑦 − 3 log 5 𝑧
𝑧
(From division to subtraction and vice versa-> Quotient Rule; and the exponent to a co-
efficient-> Power Rule)

1
1
c. log 3 √𝑥𝑦 = log 3 (𝑥𝑦)2 = (log 3 𝑥 + log 3 𝑦) ->For the square root, we use the laws of
2
exponents. In which, the square root is the same as having a power of ½. Then turning the
exponent to a co-efficient before the log (Power Rule). Then expanding the inside using the
Product Rule.

For example,

1) log 2 (32 𝑥 5 𝑦 2 ) = log 2 (32) + log 2 ( 𝑥 5 ) + log 2 (𝑦 2 ) = log 2 32 + 5 log 2 𝑥 + 2 log 2 𝑦


12 𝑤 5 12 𝑤 5 1
2) log 2 ( ) = log2 ( 1 ) = log 2 12 + 5 log 2 𝑤 - log2 𝑦
√𝑦 𝑦2
2
Expressing expanded logs as a single logarithm
𝑥𝑦
a. log 2 𝑥 + log 2 𝑦 - 3 log 2 𝑧 = log 2 ( ) -> Quotient Rule
𝑧3

b. 3 log 4 𝑥 + 2 log 4 𝑦 = log 4 𝑥 3 𝑦 2 -> Product Rule


1 1 √𝑥
c. log 5 𝑥 – 3 log 5 𝑦 = log 5 [ 3 ] -> using the Laws of Exponents
2 √𝑦

d. log 5 500 − 2 log 5 2 + log 4 32 + log 4 8 -> log 5 500 − log 5 22 + log 4 32 + log 4 8
-> log 5 500 − log 5 4 + log 4 32 + log 4 8
500
-> log 5 ( ) + log 4 (32 ∙ 8)
4

log 5 500 − 2 log 5 2 + log 4 32 + log 4 8 = log 5 125 + log 4 256

Logarithmic Equations- are equations involving the logarithmic expression 𝐥𝐨𝐠 𝒂 𝑼.


There are 2 Types of Logarithmic Equations:

e.g.
1. Find the solution set of log (𝑥 − 5) = 2
To solve logarithmic equations, we shall use the definition of logarithms: y=𝐥𝐨𝐠 𝒃 𝒙, if and only if,
𝒚
𝒃 = 𝒙. Remember that: Log. is an exponent
Since log (𝑥 − 5) = 𝐥𝐨𝐠 𝟏𝟎 (𝑥 − 5) -> natural logarithm, then the exponential form is
102 = x – 5
100 = x - 5
100 +5 = x
x = 105
The solution set is {105}. Or ∴ (Therefore/Hence) x = 105.
2.) log 3 (𝑥) = −5
x = 3−5 -> use the negative exponent law 3.) log 𝑥 3 = log 27

x=
1
=
1
->
1
∴ x = 243 𝑥 3 = 27
3 5 243
3 3
√𝑥 = √27
∴x=3
4. log 3 (𝑥) + log 3 (𝑥 − 2) = log 3 (𝑥 + 10)
 Apply Product Rule from Log Rules-> log 3 [𝑥(𝑥 − 2)] = log 3 (𝑥 + 10)
log 3 [𝑥 2 − 2𝑥] = log 3 (𝑥 + 10)
 Drop the logs, set the arguments (stuff inside the parenthesis) equal to each other
𝑥 2 − 2𝑥 = 𝑥 + 10
 Solve the quadratic equation using factoring method. But you need to move everything on one side
while forcing the opposite side equal to 0.
𝑥 2 − 2𝑥 − 𝑥 − 10 = 0
𝑥 2 − 3𝑥 − 10 = 0
(𝑥 − 5)(𝑥 + 2) = 0
 Set each factor equal to zero then solve for x.
𝑥−5=0  𝑥+2=0
x=5 x = -2
So the possible solutions are 5 and -2. Remember to always substitute the possible solutions back to
the original log equation and verify if it yields a true statement. (Check)

∴ x = 5 is the only possible solution.


Remember…
It is OKAY to have values of x such as positive, 0, and negative numbers.
However, it is NOT ALLOWED to have a logarithm of negative number and zero when substituted or
evaluated into the original logarithm equation.
log (negative number) = undefined
log (0) = undefined

5. log 𝑥 4 = −2 ⇔ 𝑥 −2 = 4

 Raise each side to -1 and Simplify.


(𝑥 −2 )−1 = 4−1
𝑥 2 = 4−1
1
𝑥2 =
4
1
𝑥2 − 4 = 0
1 1
x=± ∴x= is the only solution
2 2
6. Solve the exact solution set of 3𝑥 = 100.

 Equivalate logarithmic equation: x = log 3 100


∴ the exact solution set is { log 3 100 }.
2)
7. Solve the logarithmic equation 2(𝑥 = 4(2𝑥−2)

 Rewrite each side of the logarithmic equation as a power of the same base:
2)
2(𝑥 = 4(2𝑥−2)
2) (2𝑥−2)
2(𝑥 = 22
2)
2(𝑥 = 2(4𝑥−4)
𝑥 2 = 4𝑥 − 4
𝑥 2 − 4𝑥 + 4 = 0
(x - 2) (x - 2) = 0
x – 2 =0
x=2

8.

 Note that this is a Rational Equation. One way to solve it is to get its Cross Product/ to Cross
Multiply.

->

 Simplify both sides by the Distributive Property. At this point, we realize that it is just a Quadratic
Equation. No big deal then. Move everything to one side, and that forces one side of the equation to
be equal to zero.

3𝑥 2 − 2𝑥 2 − 6𝑥 + 𝑥 − 24 = 0

x = -3  x = 8
∴ x = 8, since negative is undefined
9.

 This problem involves the use of the symbol“ln”instead of“log”to mean logarithm.
 ln is a special kind of logarithm using base e where e ≈ 2.71828.

 Write the variable first then the constant to be ready for FOIL method

 Simplify the two binomials by multiplying them together

 Solve the Quadratic Equation using the Square Root Method. You do it by isolating the squared
variable on one side and the constant on the other. Then we apply the square root on both sides.
Don’t forget the ± symbol.

𝟏 1
The ONLY valid answer is x = 𝟐 which makes x =- 2 an extraneous answer.

10.
-> Keeping the log expression on the left, and moving all the constants on
the right side.

 To get rid of the radical symbol on the left side, square both sides of the equation.
 Check your potential answer back into the original equation. After doing so, you should be
convinced that indeed x = −104 is a valid solution. Even if you don’t, the only solution, obviously
is, -104.